Oral histoplasmosis masquerading as acute necrotizing ulcerative gingivitis: A rare case report - Khetarpal, Shaleen; Mhapsekar, Trishna; Nagar, Rahul; Parihar, Ajay (International Journal of Health Sciences, 2019)
Histoplasmosis also called as “Darling’s Disease” is a community-acquired primary pulmonary disease caused by inhalation of dust containing spores of soil-dwelling dimorphic fungi, Histoplasma capsulatum. Presentation of fungi in the oral cavity is usually rare and is generally associated with an immunocompromised state. Here, we present a rare case of histoplasmosis in an immunocompetent patient, with discrete oral presentation, that initially mimicked acute necrotizing ulcerative gingivitis. Gingival biopsy confirmed the diagnosis of histoplasmosis, which responded favorably to the initial treatment with intravenous amphotericin and later to oral itraconazole. Thus, a vigilant approach is paramount in reducing the fatality due to disease.